The Influence of the Tools of Liberalism and the Clash of Civilizations on Arabs’ Perceptions of the United States of America - Ali A Dashti; Ali Al-Kandari; Ahmed R. Alsaber; Ahmad Al-Shallal (Asian Journal for Public Opinion Research)
Adopting the Tools of Liberalism and Clash of Civilizations theories of international relations, and the vertical-horizontal media typology, this study examines the perceptions of 25,800 Arabs as expressed in a survey exploring their perceptions of violence against the United States, American citizens as “good,” President Donald Trump’s foreign policy in the Middle East, increasing economic relations with the United States, welcoming American foreign aid, and finally favoring diplomatic relationships with Israel. This study also looks at religiosity, the effectiveness of U.S. foreign aid, and the media sources influencing those perceptions. The findings suggest that religious activities and duties relating to Allah positively influence those perceptions while religion as ideology and politics negatively influence them. If the U.S. intentions in providing aid to Arabs are perceived to be benevolent and charitable, civic organizations and ordinary people are beneficiaries of aid, the United States is more likely to be seen in a positive light than if aid is perceived to benefit Arab governments. Of vertical media, newspapers have the strongest effects while TV and radio have little or none. Horizontal media have a mid-range effects. The study discusses the results in relation to implications for policy makers.